Firm Growth and Legal Environment. (21st January 2018) - Miroshnychenko, Ivan; Bozzi, Stefano; Barontini, Roberto
Abstract : An effective country‐level legal environment is crucial for promoting access to finance, development, and ultimately economic growth. Based on a sample of large companies listed in Continental Europe in the period 2002–2011, this study suggests that investor protection level is related to firm growth. Specifically, investor protection: a) enhances the growth rate of the firm; b) affects growth sensitivity to leverage and cash flow. These results provide empirical support to recommendations by policy makers advocating for increased investor protection in Europe.